Octodon degus: A Model for the Cognitive Impairment Associated with Alzheimer's Disease. (27th May 2013) - Tarragon, Ernesto; Lopez, Dolores; Estrada, Cristina; Ana, Gonzalez‐Cuello; Schenker, Esther; Pifferi, Fabien; Bordet, Regis; Richardson, Jill C.; Herrero, Maria Trinidad
Summary Octodon degus (O. degus) is a diurnal rodent that spontaneously develops several physiopathological conditions, analogous in many cases to those experienced by humans. In light of this, O. degus has recently been identified as a very valuable animal model for research in several medical fields, especially those concerned with neurodegenerative diseases in which risk is associated with aging. Octodon degus spontaneously develops β‐amyloid deposits analogous to those observed in some cases of Alzheimer's disease (AD). Moreover, these deposits are thought to be the key feature for AD diagnosis, and one of the suggested causes of cell loss and cognitive deficit. This review aims to bring together information to support O. degus as a valuable model for the study of AD.